Regiões circulares e o número Pi - Pereira, Thiago Veríssimo (2014)
Throughout history in various situations was necessary to determine the area of a circle and those moments mathematicians were led to test their creativity and skills. There were several ways to determine the area of a circular region developed until today. Some theory was created, directly or indirectly, related to this issue as the problem of squaring the circle and the number pi.